2022
DOI: 10.1038/s41467-022-29293-6
|View full text |Cite
|
Sign up to set email alerts
|

A natural timeless polymorphism allowing circadian clock synchronization in “white nights”

Abstract: Daily temporal organisation offers a fitness advantage and is determined by an interplay between environmental rhythms and circadian clocks. While light:dark cycles robustly synchronise circadian clocks, it is not clear how animals experiencing only weak environmental cues deal with this problem. Like humans, Drosophila originate in sub-Saharan Africa and spread North up to the polar circle, experiencing long summer days or even constant light (LL). LL disrupts clock function, due to constant activation of CRY… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Mai179-GAL4, UAS-cyc DN , Clk9M-GAL4, and Clk4.1-Gal4 have been outcrossed for 5 generations to iso31 to standardize the genomic background [55]. We recently showed that only flies carrying at least one copy of the natural ls-tim allele, encoding both the light sensitive S-TIM and less light sensitive L-TIM protein [27] are able to synchronize to temperature cycles in constant light, while flies homozygous for the s-tim allele (encoding only S-TIM) cannot [27]. Therefore, all strains analyzed in this study carry at least one copy of ls-tim.…”
Section: Fly Strainsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mai179-GAL4, UAS-cyc DN , Clk9M-GAL4, and Clk4.1-Gal4 have been outcrossed for 5 generations to iso31 to standardize the genomic background [55]. We recently showed that only flies carrying at least one copy of the natural ls-tim allele, encoding both the light sensitive S-TIM and less light sensitive L-TIM protein [27] are able to synchronize to temperature cycles in constant light, while flies homozygous for the s-tim allele (encoding only S-TIM) cannot [27]. Therefore, all strains analyzed in this study carry at least one copy of ls-tim.…”
Section: Fly Strainsmentioning
confidence: 99%
“…Strikingly, temperature cycles are able to overcome LL-induced arrhythmicity in flies carrying a recently evolved allele of the tim gene, called ls-tim [ 22 , 26 , 27 ]. In contrast, flies bearing the original s-tim allele behave arrhythmic during temperature cycles in LL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, differences in clock gene expression rhythms were linked to caste-specific activity phenotypes in ants 26 . Comparisons of fly strains and species from different latitudes further indicate that behavioral rhythmicity depends on the localization of circadian core clock genes expression in the brain 32, 34 and clock gene alleles 35, 36 . Furthermore, behavioral phenotypes including arrhythmicity can also depend on the circadian clock output pathways 33 .…”
Section: Introductionmentioning
confidence: 99%